Rhizobacteria AK1 remediates the toxic effects of salinity stress via regulation of endogenous phytohormones and gene expression in soybean. Issue 16 (30th August 2019) - Khan, Muhammad Aaqil; Asaf, Sajjad; Khan, Abdul Latif; Jan, Rahmatullah; Kang, Sang-Mo; Kim, Kyung-Min; Lee, In-Jung
Abstract : Salinity stress adversely affects the growth and productivity of different crops. In the present study, we isolated the rhizospheric bacteria Arthrobacter woluwensis AK1 from Pohang beach, South Korea and determined its plant growth-promoting potential under NaCl salt stress (0, 100, and 200 mM). AK1 has phosphate-solubilizing activity and produce siderophores, organic acids, and phytohormones such as gibberellic acid (GA) and indole-3-acetic acid (IAA) that significantly alleviate sodium chloride (NaCl) stress and increase all plant growth attributes. Furthermore, inoculation of AK1 significantly decreased endogenous abscisic acid (ABA) content, extensively regulated the antioxidant activities and mitigated NaCl stress. Similarly, inductively coupled plasma mass spectrometry results showed that soybean plants inoculated with AK1 significantly decreased the amount of sodium (Na + ) uptake during NaCl stress after 6 and 12 days. Four genes, auxin resistant 1 ( GmLAX1 ), potassium channel AKT2 ( GmAKT2 ), soybean salt tolerance 1 ( GmST1 ), and salt tolerance-associated gene on chromosome 3 ( GmSALT3 ) were up-regulated, while two genes chloride channel gene ( GmNHX1 ) and Na + /H + antiporter ( GmCLC1 ) were down-regulated in soybean AK1treated plants. In conclusion, AK1 can mitigate salinity stress, increase plant growth and could be utilized as an eco-friendly bio-fertilizer under salinity stress.